The influence of religious belief and sociocultural on breastfeeding practice: A literature review - Jamil, Nurul Akma (Malaysian Journal of Nursing, 2018)
Socio-cultural poses as the enabler and barrier in breastfeeding practice. A review of published literature was conducted and a total of 25 articles were reviewed to seek the answer: How religious belief and sociocultural influence breastfeeding practice? Published articles were identified through electronic searches of PubMed/MEDLINE, Scopus, Google scholars and IIUM Repository within timeframe of 2011 to 2017. Through this searching, three key themes were identified: religious views on breastfeeding, sociocultural perspectives and challenges. A comprehensive understanding on religious recommendation and cultural influence would benefit in the reconstruction of breastfeeding promotion and education program.